Factores que afectan el contenido de sólidos en leche - Campabadal, Carlos (Universidad de Costa Rica, 2013)
Factors affecting milk solid content. The solid content of the milk is affected by a genetic and environmental factor, which include the age of the cow, environmental temperature, milking management, health of the cow and feeding management. The factor that produces the biggest change in the solid content of the milk is the feeding management. Milk fat content can be affected between 2 to 3 units, protein content 0.1 to 0.3 units; however lactose and mineral content in constant and is not affected by the factors affecting total milk components. The principal factor that affect milk fat content is the feeding management of the cow, which include the forage: concentrate ratio, quality and particle size of the forage, type of concentrate, fatty acids content, buffers, feeding management and other additives.